Effectiveness of an electronic hand hygiene monitoring system in increasing compliance and reducing healthcare-associated infections. (September 2021) - Knudsen, A.R.; Kolle, S.; Hansen, M.B.; Møller, J.K.
Summary: During an interventional study in a nephrology department, we investigated the effect of an electronic hand hygiene monitoring system on the hand hygiene compliance of healthcare workers ( N  = 99) and hospital-acquired bloodstream infections. The hand hygiene compliance of the doctors and nurses improved significantly during the intervention phase when they received group and individual feedback based on actionable insights from the electronic hand hygiene monitoring system. The improvements in hand hygiene compliance were associated with a significant reduction in the number of hospital-acquired bloodstream infections.